The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1590/s0101-81751995000100016
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of the ovary of Columba livia (Gmelin) (Columbidae, Columbiformes)

Abstract: ABSTRACT. The study of the female genital system of Colt/mba /ivia (Gmelin, 1789) is part of the research on the reproductive biology of Brazilian birds. This work describes the morphological aspects of the ovary of Coillmba livia, as well as the histological differences observed in the ovarian follicles during the ovocyte maturation process. Ten Coillmba Jivia females were studied, whose ovaries had been dissected, fixed in Bouin and Helly solutions, and histologically processed for staining (Hematoxylin-Eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
5
0
4
Order By: Relevance
“…The medulla was comprised of loose connective tissue, smooth muscles and large number of blood vessels, fibers, lymph vessels and lacunar channels as reported earlier by Ribeiro [18] in pigeon. With advancing age, these lacunar channels increased and became wider as reported earlier by Gonzalez Moran [19] in chicken.…”
Section: Medullasupporting
confidence: 57%
See 2 more Smart Citations
“…The medulla was comprised of loose connective tissue, smooth muscles and large number of blood vessels, fibers, lymph vessels and lacunar channels as reported earlier by Ribeiro [18] in pigeon. With advancing age, these lacunar channels increased and became wider as reported earlier by Gonzalez Moran [19] in chicken.…”
Section: Medullasupporting
confidence: 57%
“…At 8 weeks of age, there was clear cut demarcation between cortex and medulla ( Figure 1). Similarly, Ribeiro [18] reported that before the gonadal maturation, there were two distinct regions in the ovary: the cortex, a peripheral region where the follicles were found and the medulla region, more central and made of loose connective tissue intensely vascularized and presenting nervous fibers and some smooth muscular fibers in pigeon. At 16 weeks, cortex started to interact with sub cortical medulla (Figure 2).…”
Section: Cortex and Medullamentioning
confidence: 88%
See 1 more Smart Citation
“…A espécie Columba livia, em específico, é bastante encontrada em países da América do Sul, tais como Brasil, Bolívia, Chile e Peru (RIBEIRO et al, 1995).…”
Section: Introductionunclassified
“…O estudo dos pombos é importante por diversos aspectos: 1) ecológicos, por serem aves onívoras que habitam diversos ambientes, inclusive grandes cidades; 2) sociais, por entupirem calhas, apodrecerem forros de madeira e causarem danos a monumentos históricos e pinturas de carros; 3) epidemiológicos, por alojarem parasitas e transmitirem doenças como Toxoplasmose, Criptococose, Ornitose, Histoplasmose e Salmonelose, além de dermatites (RIBEIRO et al, 1995).…”
Section: Introductionunclassified